Exploring the making of meaning: environmental education and training for industry, business and local government - Jenkin, Nicola Pat (Rhodes University, Faculty of Education, Department of Education, 2000)
The aim of this research was to explore how participants made meaning in an environmental education and training course for people from industry, business and local government in South Africa, and to identify and comment on any constraints to this meaning-making. I used a Symbolic Interactionist theoretical framework to explore and comment on the meaning-making process. I started my research by conducting a questionnaire to select participants for interviews. During the course the selected participants were interviewed, as well as the two course co-ordinators. Data was also gathered during the course from participant observation field notes ('captured talk'), photographs, participants' assignments and course evaluations. The data was analysed using an adapted form of discourse analysis and matrices. The research highlights that the opportunities provided on the course were adequate for encouraging meaning-making amongst both the co-ordinators and participants. However, recorded instances of meaning-making were low, which indicated that there were certain constraints during the meaning-making process. This research highlights and comments on identified constraints such as time and workplace support. The research supports similar findings which emerged from research conducted on the Gold Fields environmental education course for teachers and also offers recommendations for further research and practice into meaning-;making within the field of environmental education and industry, business and local government in South Africa.
Keywords: Environmental education; Corporations -- environmental aspects; Local government -- environmental aspects; Managerial economics -- environmental aspects